Proteomics approach of meat science: Comparison of protein profile between Malaysia organic and inorganic chicken - Muhamad Bunnori, Noraslinda; Md Zin, Noor Hasniza; Mohd Daud, Jamaluddin; Abu Hassan, Muhamad Shafiq; Saidin, Muhammad Syazwan; Nik Ahmad Kamil, Nik Nornadhirah; Hamdan, Nurul Ashima (IIUM, 2015)
Rapid juvenile growth among broilers may induce health defects including stress and metabolic diseases that can alter the expression of the protein in various parts of the body. In this study, the differences in protein expression from chicken liver and muscle between fast growing commercial broilers (CB) and slow growing indigenous chicken (IC) have been analyzed using SDS-PAGE and 2D-PAGE. In the liver, six spots were successfully identified differentially expressed in term of intensity. Those proteins are phosphoenolpyruvate kinase (PEPCK) (2 spots), delta-1-pyrolline-5-carboxylate (P5CDH), soluble epoxide hydrolase (sEH), heat shock protein 90 (HSP90) and actin. PEPCK and P5CDH enzymes were expressed higher in CB compared to IC, suggesting the utilization of alternative metabolic pathways for broilers’ energy metabolism. The sEH expression was found higher in CB compared to IC indicating the process of xenobiotic metabolic activity to eliminate harmful epoxide inside CB liver. HSP90 was found less in CB compared to IC, which might indicate the lack of regulation of heat stress response in CB. The higher expression of actin in IC liver has suggested a good form of structure integrity and good management of bile flows facilitation in IC liver. All of these findings showed that IC might have a better liver and metabolic activity compared to CB. In the muscle, six differentially expressed spots between both samples were successfully identified. Those six proteins are alpha-enolase, pyruvate kinase, heat shock 70 kDa protein, stress-induced phosphoprotein, myosin regulatory light chain and myozenin. In general, it is suggested that CB may suffer from hypoxia or prolong exercise, which was shown through the shifted metabolic activity from aerobic towards anaerobic metabolism. Moreover, CB muscle was likely to utilize 'glucose-compensation' pathways to fuel the cellular after glucose deprivation. It is also found that CB may endure from heat stress compared to IC. In term of meat quality, CB muscle has a lack of structural proteins composition compared to IC. It might be suggested that CB meat is tender compared to IC due to the lack of this structural proteins. To summarize, it is found that there are differences in protein expression when comparing slow growing IC to the fast growing CB in liver and muscle. Most of the proteins differentially expressed are involved in energy metabolism, stress regulation, and cellular structure.